Evaluasi Usability pada Aplikasi Instagram Menggunakan Metode Usability Testing - Muhammad Qomarul Huda; Rizqi Mustafa Maulana (Indragiri Islamic University, 2023)
Social media is one of the platforms that is often used by people to interact and communicate with one another. Instagram is a social media platform that allows users to post photos and videos online at high speed. This study uses the usability testing method. Usability is used to measure quality based on user experience when interacting and using applications. The calculation results of the System Usability Scale (SUS) involving 50 respondents showed a score of 77.6. From this score, it can be concluded that the interpretation of the approach based on the nature (Adjective) shows that the service belonging to the Instagram application is still included in the GOOD category.